Surfactants and interfacial phenomena - Rosen, Milton J.; Kunjappu, Joy T. (Hoboken, N.J. : Wiley, 2012)
"This book provides an easy-to-read, user-friendly resource for industrial chemists and a text for classroom use, and is an unparalleled tool for understanding and applying the latest information on surfactants. Problems are included at the end of each chapter to enhance the reader's understanding, along with many tables of data that are not compiled elsewhere. Only the minimum mathematics is used in the explanation of topics to make it easy-to-understand and very user friendly"--
Now in its fourth edition, Surfactants and Interfacial Phenomena explains why and how surfactants operate in interfacial processes (such as foaming, wetting, emulsion formation and detergency), and shows the correlations between a surfactant's chemical structure and its action. Updated and revised to include more modern information, along with additional three chapters on Surfactants in Biology and Biotechnology, Nanotechnology and Surfactants, and Molecular Modeling with Surfactant Systems, this is the premier text on the properties and applications of surfactants. This book provides an easy-to.
V. SOME USEFUL GENERALIZATIONSVI. ELECTRONIC SEARCHING OF THE SURFACTANT LITERATURE; REFERENCES; PROBLEMS; 2: Adsorption of Surface-Active Agents at Interfaces: The Electrical Double Layer; I. THE ELECTRICAL DOUBLE LAYER; II. ADSORPTION AT THE SOLID-LIQUID INTERFACE; A. Mechanisms of Adsorption and Aggregation; B. Adsorption Isotherms; 1. The Langmuir Adsorption Isotherm; C. Adsorption from Aqueous Solution onto Adsorbents with Strongly Charged Sites; 1. Ionic Surfactants; 2. Nonionic Surfactants; 3. pH Change; 4. Ionic Strength; 5. Temperature.
Machine generated contents note: Preface 1. Characteristic Features of Surfactants 2. Adsorption of Surface-Active Agents at Interfaces: The Electrical Double Layer 3. Micelle Formation by Surfactants 4. Solubilization by Solutions of Surfactants: Micellar Catalysis 5. Reduction of Surface and Interfacial Tension by Surfactants 6. Wetting and Its Modification by Surfactants 7. Foaming and Antifoaming by Aqueous Solutions of Surfactants 8. Emulsification by Surfactants 9. Dispersion and Aggregation of Solids in Liquid Media by Surfactants 10. Detergency and Its Modification by Surfactants 11. Molecular Interactions and Synergism in Mixture of Two Surfactants 12. Gemini Surfactants 13. Surfactants in Biology 14. Surfactants in Nanotechnology 15. Surfactants and Molecular Modeling Answers to Selected Problems Index.
Includes bibliographical references and index.
Print version record.
Keywords: Surface active agents; Surface chemistry; Surface active agents; Surface chemistry; Surface properties; TECHNOLOGY & ENGINEERING -- Chemical & Biochemical; Surface active agents; Surface chemistry; Electronic books; Electronic books